Waspadailah Terhadap Ancaman Teroris Dan Teror Bom dilengkapi dengan PERPU No.1 Th.2002 ... - TURAN, Achmad (CV. Amalia Bhakti Jaya, 2002)
Waspadailah Terhadap Ancaman Teroris Dan Teror Bom dilengkapi dengan : ...